Quadractic regression for water contents in the function of soil compaction - Fernandes, Barbara Barreto; Marasca, Indiamara; Martins, Murilo Battistuzzi; Sandi, Jefferson; Lanças, Kleber Pereira [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
The objective of this work was to evaluate the influence of water content in the evaluation of mechanical resistance to soil penetration measured through the cone index. The experiment was carried out at UNESP / FCA, Botucatu / SP, being selected two classes of soil: a Nitossolo Vermelho distroférrico and a Latosolo Vermelho. A completely randomized design was used, with the following compaction treatments: T0 = 0; T1 = 1; T2 = 2; T3 = 3; T4 = 5 and T5 = 10 consecutive passes of an agricultural tractor. A hydraulic-electronic penetrometer was used to sample the mechanical resistance of the soil to penetrate the layers; 0.00 – 0.10; 0.10-0.20; 0.20-0.30; 0.30-0.40 m in 4 water content conditions. With the increase in traffic, greater was the compression. However, for the clayey soil, from a tractor pass, the penetration resistance values had a small increase, not differing statistically for the most superficial layer (0-0.20m) and for the 0.20-0.40m layer from two passes. For medium textured soil, this happened from one pass to the most superficial layer (0-0.20m) and five passes to the 0.20-0.40m layer.
Regressão quadrática para teores de água em função da compactação do solo
Keywords: Aggregation; Moisture; Soil resistance